KEEPING FILE AUTHENTICITY WITH DIGITAL SIGNATURE TECHNIQUE USING A COMBINATION OF MD5 AND ELGAMAL ALGORITHM - Dandi Herman Dinata; Nova Mayasari; Rio Septian Hardinata (INFOKUM, 2022)
This study aims to maintain the authenticity of the file to provide assurance to the recipient that the data is free from modifications made by other parties. If there is a modification to the file, then the recipient will know that the file is no longer authenticated, so that the recipient of the file avoids using the wrong data. To maintain the authenticity of the data, a digital signature technique is used using the MD5 algorithm as a hash function algorithm to generate a message digest, and the Elgamal algorithm as a public key algorithm that forms the digital signature of the message digest. The combination of the two algorithms will produce a digital signature for each file that can ensure the authenticity of the file.